Effect of core density on the low-velocity impact response of foam-based sandwich composites. (1st May 2020) - Feng, D.; Aymerich, F.
Abstract: The paper presents the results of an investigation into the effect of core density on the low-velocity impact response of foam-based sandwich composites. Drop-weight tests were conducted on sandwich panels with carbon/epoxy facesheets and a 10 mm thick PVC foam core. Three foam core densities (65, 100 and 160 kg/m 3 ) and two facesheet layups ([0/903 /0], [03 /±45]S ) were examined in the study. The analyses show that the influence of core density on the damage resistance of the panels is strongly correlated to the layup of the skin. While the damage developing in [0/903 /0] panels is not affected by core density, the damage area in [03 /±45]S panels reduces with increasing core density. The different influence of core properties on the damage response of [0/903 /0] and [03 /±45]S sandwich panels may be attributed to the different bending stiffness of the facesheets, with a response to impact dominated by global bending in panels with thin [0/903 /0] skins as opposed to one mainly governed by local shear rigidity in panels with thicker [03 /±45]S skins. FE analyses were finally carried out to assess the capability of a model developed by the authors to capture the role of foam density in the impact damage response of the panels.